2013
DOI: 10.1016/j.pneurobio.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Ethics in prion disease

Abstract: This paper is intended to discuss some of the scientific and ethical issues that are created by increased research efforts towards earlier diagnosis, as well as to treatment of, human prion diseases (and related dementias), including the resulting consequences for individuals, their families, and society. Most patients with prion disease currently are diagnosed when they are about 2/3 of the way through their disease course (Geschwind, Kuo et al. 2010; Paterson, Torres-Chae et al. 2012), when the disease has p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 159 publications
(248 reference statements)
0
8
0
5
Order By: Relevance
“…Tikvah Alper, Ian Pattison, and others postulated that the “scrapie agent” did not contain nucleic acid and might be a protein. 5,6 Researchers later showed that transmission of the transmissible spongiform encephalopathy causative agent from animal to animal could be prevented by treating the tissue using methods that destroy and denature proteins. 5,6 Stanley Prusiner received the 1997 Nobel Prize in Physiology or Medicine in part for isolating the scrapie agent and confirming it was a misfolded protein, which he called a “proteinaceous infectious particle,” or prion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tikvah Alper, Ian Pattison, and others postulated that the “scrapie agent” did not contain nucleic acid and might be a protein. 5,6 Researchers later showed that transmission of the transmissible spongiform encephalopathy causative agent from animal to animal could be prevented by treating the tissue using methods that destroy and denature proteins. 5,6 Stanley Prusiner received the 1997 Nobel Prize in Physiology or Medicine in part for isolating the scrapie agent and confirming it was a misfolded protein, which he called a “proteinaceous infectious particle,” or prion.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Researchers later showed that transmission of the transmissible spongiform encephalopathy causative agent from animal to animal could be prevented by treating the tissue using methods that destroy and denature proteins. 5,6 Stanley Prusiner received the 1997 Nobel Prize in Physiology or Medicine in part for isolating the scrapie agent and confirming it was a misfolded protein, which he called a “proteinaceous infectious particle,” or prion. 5 Although Dr Prusiner’s “prion hypothesis” has been controversial for many years, accumulating evidence over the past several years has confirmed the prion hypothesis beyond any reasonable doubt.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 85-90 % of CJD cases are sporadic (sCJD) lacking any mutations in the prion protein gene (PRNP), while about 10-15% of the disorders are inherited. 1 Familial CJD (fCJD) is associated with at least 20 distinct genetic mutations that are all transmitted as autosomal dominant traits, including point, deletion and insertion mutations. 2 Most of the mutations that cause fCJD, are heterozygous.…”
Section: Introductionmentioning
confidence: 99%
“…To date, all completed clinical trials in prion disease have recruited only symptomatic patients, mostly with sporadic prion disease, and have used cognitive, functional, or survival endpoints [7][8][9][10][11][12][13][14] . By the time of diagnosis many prion disease patients are in a state of advanced dementia, and even a therapy that halted the disease process entirely at this stage might only preserve the patient in a state with little or no quality of life 15 . Moreover, preclinical proofs of concept argue that a preventive, rather than therapeutic, approach is more likely to be effective.…”
Section: Introductionmentioning
confidence: 99%